Comparative Analysis of Capital Structure Decisions - Bawa, Jaslene; Basu, Sankarshan; Nevatia, Ujvin (Economic and Political Weekly, 2024)
This research investigates the shifts in the capital structure of publicly traded firms in both developed and developing nations throughout the phases of the COVID-19 pandemic. Examining data spanning from 2015 to 2023, the study analyses 350 US firms, comprising 2,800 firm-year observations from the S&P-500, and 209 Indian firms, encompassing 1,672 firm-year observations from NIFTY-500. The findings highlight contrasting responses to the crisis: Indian companies, amid heightened uncertainty, reduced debt levels, actively repaying debts to mitigate bankruptcy risks, and exploring alternative funding avenues like equities. Conversely, US firms increased debt levels, capitalising on easier market access and low interest rates. The analysis also reveals varied associations between firm characteristics and debt levels across the two countries.
Keywords: Bankruptcy Risks; Publicly Traded Firms; COVID-19 Pandemic